Application of succession representation in peruvian law: difficulties and complications - Zuta Vidal, Erika (2024)
The representation under the Law of Succession originated with the purpose of protecting a lineage of descendants whose ascendant was entitled to inherit, but did not do so. This representative and important figure of the Law of Succession has faced numerous problems and complications.In this respect, this article will define the concept of inheritance, its requirements and legal nature, as well as its limitations and its jurisprudential development.